Posouzení informačního systému firmy a návrh změn - Vidlák, Jiří (Vysoké učení technické v Brně. Ústav soudního inženýrství, 2018)
Tato diplomová práce se zabývá analýzou současného stavu informačního systému společnosti Hutchhouse. Díky analýze současného stavu tohoto systému a návrhům opatření informačního systému by měla společnost dosáhnout lepších výsledků. Předmětem práce je nejprve analýza samotné společnosti a dále analýza informačního systému a identifikace rizik. Výstupem práce jsou opatření, díky kterým jsou tato rizika eliminována.

The diploma thesis deals with the analysis of current situation of information systém Hutchhouse’s company. Due to the analysis of the current situation of the system and due to suggestions of preventions for the information system should the compan achieves better results. The subject of the thesis is mainly a analysis of the company, then the analysis of the information system and identification of risks. Output of this diploma thesis are preventions which eliminate these risks accordingly.
Assessing an Information System of a Company and Proposing Changes
Keywords: Informační systém; SWOT analýza; HOS analýza; Skórovací metoda; Information system; SWOT analysis; HOS analysis; Scoring method